Promosi Jasa Menjahit Berbasis Web dengan Fitur Live Chat (Studi Kasus Okta Tailor): Array - Yani Siahaan, Clara Martha; Rahman Syahputra, Edy; Nurjamiyah, Nurjamiyah (Universitas Harapan Medan, 2020)
Live chat applications have become an attraction for smartphone users. Live chat application users can communicate with fellow users without any time and distance restrictions. So that it can make it easier for users to communicate between fellow users. The development method in building a Web-Based Sewing Service Promotion with the Live Chat Feature Okta Tailor Case Study is based on the agile method. The agile method consists of planning, namely the plan for making the system, requirements analysis, which is to analyze the making of the application content, design, namely to describe the appearance of the application, testing, namely for application testing, and documentation, namely to document the application results. The purpose of this research is to produce Web-Based Sewing Services Promotion with Live Chat Feature for Okta Tailor Case Studies, with the application of this system to expand the sewing service business on Okta Tailor.